Patients' experiences of pre and intra operative nursing care in Ghana: A qualitative study. (2017) - Adugbire, Bernard Atinyagrika; Aziato, Lydia; Dedey, Florence
Abstract: Objective: The objective of this study was to explore surgical patients' experiences of preoperative and intraoperative nursing care. Materials and methods: The study was conducted at the Regional Hospital, Bolgatanga, Ghana and employed a qualitative explorative descriptive design. Purposive sampling technique was used to recruit participants. The data was saturated with 15 participants aged between 23 and 65 years. All the interviews were audio-taped and transcribed verbatim. Results: The nurses reassured, counseled and pre-habilitated patients where necessary. They also provided physical care to patients but failed to involve patients in their care. Nurses did not take patients' medical history. Nurses poorly managed patients' pain during surgery and safety measures were not adequately employed resulting in some patients sustaining minor injuries due to poor usage of theatre equipment such as diathermy machines. Nurses also provided inadequate information to patients and this resulted in patients being confused and anxious. Conclusions: The study showed that some nurses require further training to provide better care to their surgical patients.